EFEK SITOTOKSIK DAN ANTIPROLIFERATIF EKSTRAK ETANOL UMBI UBI JALAR UNGU (Ipomoea batatas L) TERHADAP SEL LINE KANKER PAYUDARA T47D 1 - Sumardika, I Wayan; Wiwiek Indrayan, Agung; Jawi, I Made; Suprapta, Dewa Ngurah; Adnyan, Losen (journal of internal medicine, 2012)
Cancer is still one of the leading death causes worldwide. Consuming antioxidants can reduce the cancer incidence. Anthocyanin that contained in purple sweet potatoes can inhibit DNA damages. In order to prove the activity of purple sweet potatoes on cancer cell, it is necessary to have some direct research on cancer cell line. This study is a simple experimental research method. The activities of the anticancer are evaluated from cytotoxic and antiproliferative effects on cell line breast cancer T47D. Cytotoxic effects is examined with cultured cell stained with tryphan blue exlusion. Each well are contain of 36,000 cells, which is given ethanol extract purple sweet potatoes with 10 dose variation starting from 500  g/mL up to 10,000  g/mL replicated three times, then the inhibitory percentage is calculated. Antiproliferative activity is evaluated by incubating cancer cells that have been given ethanol extract purple sweet potatoes in 3 doses variation; 500, 1,000 and 2,000  g/ml in 24, 48 and 72 hours. Result of this study showed that ethanol extract purple sweet potatoes had cytotoxic activities on T47D breast cancer cell line in these dose variations, 500; 1,000; 2,000; 3,000; 4,000; 5,000; 6,000; 7,000; 8,000; 9,000 and 10,000  g/ml. The cytotoxic activity on each of dose variations above are 27.56; 42.67; 57.78; 66.67; 72.44; 79.56; 85.33; 87.56; 92.44;100; and 100 %. Ethanol extract purple sweet potatoes showed antiproliferative activities on T47D breast cancer cells in 24, 48, 72 hours incubation in concentrations 500; 1,000; and 2,000  g/ml; those are 35,700; 29,800; 25,500 cells (24 hours); 72,500; 60,300; 52,600 cells  (48 hours); 149,500;122,600;107,300 cells  (72 hours). In conclusion, ethanol extract purple sweet potatoes had cytotoxic and antiproliferative activities on cell line breast cancer T47D.
Keywords: ethanol, extract purple sweet potatoes, breast cancer